How Does Procedural Fairness Affect Performance Evaluation System Satisfaction? (Evidence from a UK Police Force) - Mahfud, Sholihin (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
This paper investigates whether, and if so, how procedural fairness affects performance evaluation system satisfaction in a UK Police Force. Employing a survey method with samples of detective inspectors and detective chief inspectors with significant managerial responsibilities in a UK Police Force, this study finds that procedural fairness affects performance evaluation system satisfaction. Further analysis reveals that the effect of procedural fairness on performance evaluation system satisfaction is mediated by trust. This study provides empirical evidence on how procedural fairness affects performance evaluation system satisfaction. The results of this study may benefit the designer of performance evaluation systems in police organizations.Â